Family health task implementation and the health status of diabetes mellitus patients: A correlational study - Niko Dima Kristianingrum Kristianingrum; Delfira Arizda; Setyoadi Setyoadi; Yati Sri Hayati; Michael Leo Parchman (PAGEPress Publications, 2023)
Introduction: Chronic conditions due to diabetes cause changes in patients' health status and their family has importantroles in the health care. Therefore, this study aimed to analyze the relationship between family health task implementation and the health status of diabetics. Design and methods: An observational analytic design with a cross-sectional approach was used, while the respondents consisted of 327 family caregivers and 327 diabetes mellitus patients. This study used both family health task implementation and Short Form Health Survey (SF-12) questionnaires. Results: The result of the Pearson Product Moment test showed a correlation coefficient of 0.593 and a 0.000 p-value (α 0.05). Conclusions: It was concluded that there was a fairly strong relationship between family health task implementation and the health status of diabetes mellitus patients. Nursing intervention is needed to improve the implementation of family health tasks.